2018
DOI: 10.2139/ssrn.3131619
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Community Engagement on Healthcare Utilization and Health Insurance Enrolment in Ghana Results from a Randomized Experiment

Abstract: Background: Health insurance enrolment in many Sub-Saharan African countries is low, even with highly subsidized premiums and exemptions for vulnerable populations. This paper evaluates the impact of a community engagement intervention implemented in Ghana with the aim of improving clients' perceptions on service quality and subsequently improving healthcare utilization and health insurance enrolment. Method: We used a panel data of 6,937 individuals from a cluster randomized controlled trial conducted in 64 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Women in rural areas being more likely to subscribe to health insurance than women in urban areas is an indication of the higher need for health care services documented to exist in rural areas than in urban areas [ 40 – 42 ]. Thus, women in the rural areas were more likely to subscribe to the health insurance so as to be able to afford health care in times of need, as they may not be able to afford health care out-of-pocket if they fall sick [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women in rural areas being more likely to subscribe to health insurance than women in urban areas is an indication of the higher need for health care services documented to exist in rural areas than in urban areas [ 40 – 42 ]. Thus, women in the rural areas were more likely to subscribe to the health insurance so as to be able to afford health care in times of need, as they may not be able to afford health care out-of-pocket if they fall sick [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several service access and use outcomes were assessed as having increased on average but not statistically significantly, including service quality (SMD=0.19, 95%CI=−0.01, 0.39; 7 studies) and user satisfaction (SMD=0.13, 95%CI=−0.04, 0.30; six studies). Finally, a few single studies reported positive wellbeing outcomes for reducing illness (Duku et al, ) and crime (Palladium, ), and improving empowerment and assets (Fiala & Premand, ) (Figure ). Only one study (Fiala & Premand, ) measured state‐society relations outcomes and was not able to detect significant changes due to citizen feedback mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…User satisfaction was measured through satisfaction surveys in health (Duku et al, 2018;Gine et al, 2018), policing (Banerjee et al, 2014), general satisfaction with local amenities provided by government including infrastructure (Beuermann et al, 2014;Molina, 2014) and employment services (Ravallion et al, 2013), and complaints reported (Banerjee et al, 2018). User satisfaction with service delivery staff was also assessed in policing (Banerjee et al, 2014), health (Bradley et al, 2005;Gine et al, 2018) and family planning (Gullo et al, 2017) and in local leadership (Molina, 2014;Fiala et al, 2017).…”
Section: Service Use and Attitudes To Servicesmentioning
confidence: 99%
“…A variety of wellbeing outcomes among study participants were measured. Health outcomes included mortality (Touchton & Wampler, 2015;Bjorkman et al, 2017;Gine et al, 2018), illness (Duku et al 2018;Gine et al, 2018), fertility (Bjorkman et al, 2017;Donato & Mosqueira, 2016) and anthropometry (Bjorkman et al, 2017;Gine et al, 2018). Several studies reported agriculture yields (Bandyopadhyay et al, 2010;Huang et al, 2014) and livestock (Fiala et al, 2017).…”
Section: Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation